Speech acts tris` utterances in divergent a graduating paper submitted in partial fulfillment of the requirements for gaining the bachelor degree in english literature - Moh Nurul Huda (Faculty of Adab and Cultural Sciences State Islamic University Sunan Kalijaga, 2016)
yati 1/ws.c.1